The effect of self-rated health, subjective socioeconomic status, social capital, and physical activity on life satisfaction: a cross-sectional study in urban western Iran - Nader Rajabi Gilan; Mehdi khezeli; Shirin Zardoshtian (BMC, 2021)
Abstract Background Life satisfaction is an important component in designing strategies to improve health outcomes in different groups of society. This study aimed to investigate the effect of subjective socioeconomic status (SSS), social capital (SC), self-rated health (SRH), and physical activity (PA) on life satisfaction (LS) in Iran. Methods This cross-sectional study was conducted on 1187 people (643 men and 544 women) lived in five western cities in Iran. The sampling method was multistage clustering. Data collection tool was a five part questionnaire including demographic characteristics, socioeconomic status ladder, social capital scale, a question to measure physical activity, and the life satisfaction scale. Data were analyzed using independent t-test, one way ANOVA, and Ordinal Logistic Regression. Result Life satisfaction was higher in married men and women compared to single and widows (p < 0.05). Among the variables included in the main model, the significant predictors were college education (− 0.500), marriage (coefficient = 0.422), age 25-34 years (coefficient = − 0.384), SRH (coefficient = 0.477), male sex (coefficient = 0.425), SSS (coefficient = 0.373), trust (coefficient = 0.115), and belonging and empathy (coefficient = 0.064). Conclusion SRH and SSS were significant predictors of life satisfaction in west Iranian society. Being married was associated with higher LS, but college education affects LS adversely.